Dental Service Quality and Facilities Influence BPJS Patient Loyalty with Patient Satisfaction as Mediation at Rizkia Dental Clinic : Service Quality and Facilities Influence BPJS Patient Loyalty with Patient Satisfaction as Mediation at Rizkia Dental Clinic - Noventika, Rizkia Anisnur; Marnoto, Marnoto; Sunarto, Stephanus (Jurnal Ecoment Global, 2025)
Objective: The purpose of this study is to analyze the Quality of Dental Health Services and Facilities on BPJS Patient Loyalty with BPJS Patient Satisfaction as a Mediating Variable at Rizkia Dental Clinic. Design/Methods/Approach: The population in this study were patients who had undergone dental and oral care at Rizkia Dental Clinic Jepara in 2024. The sampling technique used was purposive sampling with a sample of 110 patients. The variables in this study included service quality, facilities, patient loyalty, and patient satisfaction. Data collection was conducted using a questionnaire/Google Form. Data analysis was carried out using SEM-PLS software. Findings: The analysis results show that the quality of dental health services and facilities significantly influence patient satisfaction at Rizkia Dental Clinic by 80.2% with a p-value <0.05. Furthermore, there is an influence of the quality of dental health services and facilities through patient satisfaction on patient loyalty at Rizkia Dental Clinic by 94.8% with a p-value <0.05. All research hypotheses are accepted, confirming the importance of quality services and adequate facilities in building patient satisfaction and loyalty. Originality/Value: The originality of this study lies in its analysis of the relationship between dental service quality and facilities and BPJS patient loyalty, with satisfaction acting as a mediator, specifically in the context of Rizkia Dental Clinic Jepara. This approach offers a new perspective that has not been widely researched in BPJS dental services. Practical/Policy implication: This study confirms that service quality and facilities affect BPJS patient satisfaction and loyalty at Rizkia Dental Clinic, with satisfaction serving as an essential mediator. Theoretical implications strengthen the literature on health service management, while managerial implications highlight the need to improve services, facilities, and follow-up care. It is recommended that the clinic regularly evaluate patient satisfaction, enhance facilities, and that future researchers expand the sample, add new variables, and apply mixed methods for more comprehensive findings.